The Effects of Probiotic Supplementation on Level of Disability, Depressive Symptoms, and Cognitive Outcomes in Relapsing-Remitting Multiple Sclerosis Patients: A Randomized Double-Blind Placebo-Controlled Trial - Amirreza Naseri; Sarvin Sanaie; Sama Rahnemayan; Reza Mosaddeghi-Heris; Malihe Talebi; Mahnaz Talebi (Pharmaceutical Sciences, 2025)
Background: Multiple sclerosis (MS) is a chronic autoimmune disease characterized by inflammation and demyelination of the central nervous system. Probiotics, through the gut-brain axis, are suggested to enhance clinical outcomes in patients with MS. This study scrutinizes the effects of probiotic supplementation in relapsing-remitting MS (RRMS) patients. Methods: In this parallel, randomized, double-blind, placebo-controlled trial, 90 RRMS patients, with Expanded Disability Status Scale (EDSS) < 4, received either the probiotic (Lactocare®) or a placebo twice daily for four months. Assessed outcomes included level of disability (based on EDSS), cognitive function (Symbol Digit Modalities Test [SDMT], three-second version of Paced Auditory Serial Addition Test [PASAT-3]), depressive symptoms (Beck Depression Inventory- II [BDI-II]), and manual dexterity (Nine-Hole Peg Test [9HPT]). Blinding was performed for outcome assessors and the patients. All assessments were conducted at baseline and after four months, and the findings compared between the groups of the study. Results: Out of 90 randomized patients, 60 completed the trial (29 in the probiotics group, 31 in the placebo group). Probiotics supplementation was not associated with significant improvement in EDSS, BDI-II, PASAT, SDMT, and non-dominant hand 9HPT (p-values > 0.05). Intragroup improvements in PASAT-3 (change median: 2 [IQR:9.5]) and dominant hand 9HPT (change median: -0.43 [IQR: 2.15]) were observed in the probiotic supplementation group, which was comparable to placebo. Conclusion: Supplementation with a seven-strain probiotics product for four months does not result in a significant improvement in depressive symptoms, cognitive performance, level of disability, and manual dexterity of RRMS patients with EDSS < 4.